2014
DOI: 10.1016/j.celrep.2014.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Nontemplated Nucleotide Additions Distinguish the Small RNA Composition in Cells from Exosomes

Abstract: Functional biomolecules, including small noncoding RNAs (ncRNAs), are released and transmitted between mammalian cells via extracellular vesicles (EVs), including endosome-derived exosomes. The small RNA composition in cells differs from exosomes, but underlying mechanisms have not been established. We generated small RNA profiles by RNA sequencing (RNA-seq) from a panel of human B cells and their secreted exosomes. A comprehensive bioinformatics and statistical analysis revealed nonrandomly distributed subset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
427
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 500 publications
(451 citation statements)
references
References 47 publications
20
427
2
2
Order By: Relevance
“…As a percentage of total miRNAs, APOB particles contained significantly more miRNAs harbouring NTAs than liver samples (Supplementary Figure 2). A previous study proposed that poly-uridylation (NTA-U) was increased on extracellular miRNAs (released in exosomes) and miRNA poly-adenylation (NTA-A) was associated with cellular retention [29]. To determine if lipoproteins and/or biofluids are similarly enriched for poly-uridylation, NTA patterns were compared between groups, and similar to exosomes, HDL and APOB samples were indeed observed to be significantly enriched with NTA-U compared to liver samples which were enriched with NTA-A (Figure 2(f)).…”
Section: Resultsmentioning
confidence: 99%
“…As a percentage of total miRNAs, APOB particles contained significantly more miRNAs harbouring NTAs than liver samples (Supplementary Figure 2). A previous study proposed that poly-uridylation (NTA-U) was increased on extracellular miRNAs (released in exosomes) and miRNA poly-adenylation (NTA-A) was associated with cellular retention [29]. To determine if lipoproteins and/or biofluids are similarly enriched for poly-uridylation, NTA patterns were compared between groups, and similar to exosomes, HDL and APOB samples were indeed observed to be significantly enriched with NTA-U compared to liver samples which were enriched with NTA-A (Figure 2(f)).…”
Section: Resultsmentioning
confidence: 99%
“…In this study we identified 1041 miRNAs altogether in the extracellular vesicle and cell samples studied, which are more than most array systems would detect. [22][23][24][25][26][27]42,43 Further, comparison among expression of miRNAs is possible with deep sequencing approaches, if the absolute number of copies in the sample can be quantified. 44 In this study, by using the Quantile normalization method for all samples, miRNA expression showed positive relationship between the samples, although many detected miRNA are unique in the different subsets of vesicles ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] Importantly, many small RNAs are released in the extracellular environment as EV cargo, which has been specifically documented for the exosomes. [22][23][24][25][26][27] Importantly, many cellular RNAs, including miRNAs are detected in the extracellular space, especially in extracellular vesicles. 28,29 Currently, extracellular RNA communication is also considered to be putatively important in animals, with important implications for biology, disease and medicine.…”
Section: Introductionmentioning
confidence: 99%
“…are enriched or underrepresented in EVs compared to their respective parent cells [36][37][38][39][40][41]. Based on these observations it is generally accepted that the composition of EVs is, at least partially, actively regulated by the parent cell [42], albeit that the mechanisms and associated key players regulating this cargo sorting remain largely elusive to date [38,[43][44][45][46]. The overall EV configuration (i.e.…”
Section: Biogenesis Cargo Loading and Compositionmentioning
confidence: 99%
“…This enrichment could even be further enhanced when miR-1289 was overexpressed in the producing cell [39]. Regarding miRNA sorting, Koppers-lalic et al discovered that 3'-uridylated miRNAs are enriched in human B cell-derived EVs [45]. Villarroya-Beltri and colleagues showed that miRNAs containing a GGAG sequence were overrepresented in primary T lymphoblast EVs.…”
Section: Loading Evs With a Therapeutic Cargomentioning
confidence: 99%